Irsogladine Prevents Monochloramine-Induced Gastric Mucosal Lesions by Improving the Decrease in Mucosal Blood Flow Due to the Disturbance of Nitric Oxide Synthesis in Rats - Takashi Kyoi; Michiko Oka; Kumiko Noda; Yojiro Ukai (Elsevier, 2003)
ABSTRACT: The inhibitory effect of an anti-ulcer drug irsogladine [2,4-diamino-6-(2,5-dichlorophenyl)-s-triazine maleate] on monochloramine (NH2Cl)-induced gastric mucosal lesions and its mechanisms of action were clarified in rats. Irsogladine dose-dependently prevented the formation of gastric mucosal lesions induced by 60 mM NH2Cl. The mucosal protective effect of irsogladine was not influenced by capsaicin-sensitive sensory defunctionalization. On the other hand, its protective effect was diminished by the inhibitor of nitric oxide synthase NG-nitro-L-arginine methylester (L-NAME), but not by the inducible nitric oxide synthase selective inhibitor aminoguanidine. Irsogladine restored the NH2Cl-induced decrease in the gastric cGMP formation as an index of nitric oxide synthesis, while it alone had no influence on the cGMP formation in intact tissues. Pretreatment with L-NAME abolished the recovery of cGMP by irsogladine. Furthermore, irsogladine ameliorated the NH2Cl-induced decrease in gastric mucosal blood flow, which was also reversed by pretreatment with L-NAME. These findings suggest that the improvement of the decrease in mucosal blood flow subsequent to the disturbance of gastric nitric oxide synthesis is involved in the protective effect of irsogladine on gastric mucosal lesions caused by NH2Cl.